Penerapan Model Quantum Learning Untuk Meningkatkan Hasil Belajar dalam Eksperimen Sederhana melalui Game pada Materi Proses Fotosintesis di Kelas IVA SD Islam Al Madina - Dewi Susilowati; Sukamto Sukamto; Novia Puji Rahayu; Khoiruliono Abdullah (Jurnal Bintang Pendidikan Indonesia, 2023)
The aim of this research is to gain a general understanding of how learning is implemented. At Al MAdina Islamic Elementary School Semarang, Indonesia, class IVA students took part in a simple experiment on the photosynthesis process using a quantum learning model to improve learning outcomes. Classroom action research (PTK), a form of research consisting of four stages: planning, implementation, observation and reflection, is a stage in each cycle. The research was carried out in two cycles, with one meeting each cycle. Student worksheets were used to collect research data. Quantitative and qualitative analysis methods are used in the data analysis process. Based on learning results, it can be seen from the pre-cycle that 14% of students completed and 86% of students did not complete. Cycle I obtained 61% completeness and 39% incomplete. Meanwhile, in cycle II, reflection was carried out so that there was an increase from cycle I with completion achievements of 93% of students completing and 7% of students not completing. By applying the Quantum Learning model in simple experiments using games, it can make students happy in participating in learning so that it can improve student learning outcomes in science subjects, especially photosynthesis process material in class IVA at Almadina Islamic Elementary School, Semarang.